The regulatory role of ELK-1 ubiquitination in cell proliferation and prostate cancer - Quintero Barceinas, Reyna Sara (2020)
Early stage Prostate Cancer (PC) is usually androgen-dependent and androgen ablation therapies have been used with good results in the destruction of androgen-dependent cells. However, anti-androgens are associated with systemic side effects and selection for tumour cells that survive in the absence of androgens, leading to androgen-independent PC.